Cross-Border Securities Clearing and Settlement Infrastructure in the European Union as a Prerequisite to Financial Markets Integration: Challenges and Perspectives - Cynthia Hirata de Carvalho (Hamburg Institute of International Economics (HWWA), 2004)
The importance of an efficient securities clearing and settlement system lies on the safer transfer of ownership of assets against payment. Such a system must be developed in a way to minimize the risks involved on securities transactions, and it must still offer lower costs, which do not hinder the intention to acquire or dispose securities. The cross-border securities clearing and settlement transactions within Europe, especially equities transactions, are still much higher and riskier than if cleared and settled domestically. The fragmented structure of local securities depositories is hindering the integration of financial markets in Europe, because investors are not stimulated to enjoy opportunities cross-border. Thus a smoothly functioning integrated infrastructure for clearing and settlement within the European Union is a precondition to further developments of the single financial market. The immediate benefits of financial integration in Europe are economic growth. Benefits under the investors' perspective are higher risk-adjusted returns on savings, better position to diversify portfolio, as well as higher liquidity and competition in the capital markets. On the other hand, corporations would also be favored with better access to financing capital, and competition would force financial intermediates to offer a wider range of financial products at lower prices.
Keywords: G21; F30; O33; 330; Securities settlement systems; settlement designs; models for consolidation of depository institutions; Wertpapiergeschäft; Wertpapierhandel; Verrechnungsverkehr; Internationaler Finanzmarkt; Marktintegration; EU-Staaten